Nursing Care For Bipolar Client At The Risk Of Suicide Using Supportive Therapy - Rosmiati, Rosmiati; Pauji Salam, Wulan Anugrah (Asy-Syifa : Journal of Science and Technology Nursing, 2024)
Purpose: The purpose of this study was to carry out comprehensive nursing care in bipolar with suicide risk using supportive therapy. Methods: descriptive case study method, by managing one client using the nursing process approach. Results: The results of the study after conducting supportive therapy on bipolar clients with suicide risk, for 5 times showed a decrease in suicide risk. Conclusion :The conclusion of this study is that supportive therapy collaborated with SP is very effective in reducing the risk of suicide